Joint time and power allocation for uplink cooperative non-orthogonal multiple access based massive machine-type communication Network - Shujun Han; Xiaodong Xu; Litong Zhao; Xiaofeng Tao (International Journal of Distributed Sensor Networks)
Non-orthogonal multiple access is an essential promising solution to support large-scale connectivity required by massive machine-type communication scenario defined in the fifth generation (5G) mobile communication system. In this article, we study the problem of energy minimization in non-orthogonal multiple access–based massive machine-type communication network. Focusing on the massive machine-type communication scenario and assisted by grouping method, we propose an uplink cooperative non-orthogonal multiple access scheme with two phases, transmission phase and cooperation phase, for one uplink cooperative transmission period. Based on uplink cooperative non-orthogonal multiple access, the machine-type communication device with better channel condition and more residual energy will be selected as a group head, which acts as a relay assisting other machine-type communication devices to communicate. In the transmission phase, machine-type communication devices transmit data to the group head. Then, the group head transmits the received data with its own data to base station in the cooperation phase. Because the massive machine-type communication devices are low-cost dominant with limited battery, based on uplink cooperative non-orthogonal multiple access, we propose a joint time and power allocation algorithm to minimize the system energy consumption. Furthermore, the proposed joint time and power allocation algorithm includes dynamic group head selection and fractional transmit time allocation algorithms. Simulation results show that the proposed solution for uplink cooperative non-orthogonal multiple access–based massive machine-type communication network outperforms other schemes.